Nilai kepahlawanan serat wedhatama dalam komik gundala son of lightning - Rizal, Muhammad Daniel Fahmi; Dewi, Liana Shinta (Aksara: Jurnal Bahasa dan Sastra, 2023)
Gundala is an Indonesian superhero character created by a comic artist from Yogyakarta named Hasmi in 1969. The author's social background makes Gundala thick with Javanese cultural values. In 2019, Gundala was retold by the duet of Is Yuniarto and Sweta Kartika in the title Gundala Son of Lightning (GSOL). The two comic artists came from Surabaya and Kebumen. This study aims to find the value of heroism in the Gundala version (GSOL) according to Serat Wedhatama. This research uses the theory of literary sociology and uses descriptive qualitative methods. The results showed that there is a new version of Gundala's heroic value which is reflected through being willing to sacrifice, humble and soothing the hearts of others, willing to lose, and patient. The conclusion is that although the character Gundala was created by a comic artist who is different from the original version, the value of Javanese culture, in this case the value of heroism, is still strongly possessed by this character.Keywords: Gundala, Sociology of Literature, Values, Heroism, Wedhatama Fiber